2013
DOI: 10.3390/en6115609
|View full text |Cite
|
Sign up to set email alerts
|

Cost and CO2 Emission Optimization of Steel Reinforced Concrete Columns in High-Rise Buildings

Abstract: Abstract:The construction industry is a representative industry that consumes large amounts of energy and produces substantial pollution. The operation of a building accounts for a large portion of its total CO 2 emissions. Most efforts are focused on improving the energy efficiency related to the operation of a building. The relative importance of the energy and CO 2 emissions from the construction materials increases with the increasing number of low-energy buildings. To minimize the life-cycle energy use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Additionally, they did not consider other construction materials, such as reinforcing bars, paint, glass, and insulating materials, although the concrete includes significant amount of CO 2 emissions. Moreover, Park et al [21] propose an optimal design method of steel reinforced concrete in high-rise buildings. They maintain that a main source of emitting carbon dioxide in construction corresponds to construction materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, they did not consider other construction materials, such as reinforcing bars, paint, glass, and insulating materials, although the concrete includes significant amount of CO 2 emissions. Moreover, Park et al [21] propose an optimal design method of steel reinforced concrete in high-rise buildings. They maintain that a main source of emitting carbon dioxide in construction corresponds to construction materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kim et al (2016) If concrete mix and raw material suppliers were carefully selected, it can be obtained a reduction of 34% in the emission of CO 2 and 1% in the costs Park et al (2012) CO 2 emissions increase linearly with the compressive strength of the concrete; to similar strengths, the concrete produced in the winter presented an increase of approximately 5% in the CO 2 emissions Santoro and Kripka (2016) Higher strength concrete will produce a greater amount of CO 2 ; the CO 2 emissions during transport are significant Choi et al (2016) For smaller loads the increase of the transversal area of concrete is more advantageous for the eduction of O 2 emissions, and for greater loads the increase of the steel profile produces a more sustainable solution Berndt (2015) The use of smaller resistances is advantageous in relation to CO 2 emissions; the choice of the concrete mixture strongly influences the magnitude of the CO 2 emissions Yang et al (2015) The intensity of CO 2 emissions gradually decreases as Portland cement is replaced by complementary cementitious materials (up to 20%) García-Segura et al (2014) In comparison to Portland cement, despite the reduction in CO 2 capture and life time, 80% blast furnace slag cement emitted 20% less CO 2 per year Cabello et al (2016) To reduce the environmental impact generated by a structure, the focus should be on phases of production of raw materials, transportation and production of concrete Oliveira et al (2014) It is not appropriate to base decisions on the emissions of concrete solely on the strength of the concrete and the type of cement used, since the variations are significant Paya-Zaforteza et al (2009) Minimization of embedded CO 2 emissions and economic cost seem to be highly related Park et al (2013) Reducing the amount of steel and increasing the amount of concrete can be an effective way to reduce the structural costs and CO 2 emissions of columns Habert and Roussel (2009) It is also possible to combine cement replacement and increase mechanical strength Possan et al (2016) Concrete during its life time can absorb from 40 to 90% of CO 2 emitted in the manufacturing process; the absorption of CO 2 is directly proportional to the surface area of concrete exposed to CO 2 , and influenced by the type of cement and resistance to concrete. Park et al (2014) Increasing the strength of the structural materials used is more efficient in reducing CO 2 emissions and costs than increasing the quantities of structural materials used Collins (2013) If carbonation is ignored, emission estimates can be overestimated by up to 45% depending on the strength of the concrete that was used as well as the type of construction application that incorporates recycled concrete during the second generation Yepes et al (2012) CO 2 emissions and costs are closely related.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…Alternatively, the approximate solutions of the best cost worsen CO 2 emissions by 3.8%. Park et al (2013) carried out a study proposing a sizing method for composite columns of reinforced concrete and steel profiles in tall buildings (35 floors), to reduce the cost and CO 2 emissions of structural materials during the construction phase. The results obtained from the proposed technique indicated that the weight of the steel section, in the best result, was reduced by 39.14% while the weight of the concrete was increased by 7.23%.…”
Section: Recent Studies On Emissions Of Carbon Dioxide Of Reinforced mentioning
confidence: 99%
“…Nmaterial is the number of materials defined in the structure design problem. CO2 emissions of the structural materials are adopted from literature studies [33], [36] which are shown in Table 1.…”
Section: Mathematical Modelmentioning
confidence: 99%